Interrogating the inflation-corruption nexus for Sub-Saharan African (SSA) countries: The case of Ghana - Stephen Emmanuel Armah; Alfred Berkoh (Social Sciences and Humanities Open)
This paper examined the corruption-inflation nexus for Ghana using both the Non-Linear Auto Regressive Distributed Lag – Error Correction Model (NARDL-ECM) and the linear ARDL-ECM and data from 1998 to 2020 for Ghana. Corruption was measured by The World Bank's Control of Corruption (COC) index, and Transparency International (TI)'s Corruption Perception Index (CPI) while data on inflation and all other covariates were obtained from the World Bank Indicators (WDI). Results confirm cointegration in the presence and absence of asymmetry in the long run but not in the short run. In comparison, no symmetry is found for the response of inflation to the exchange rate. Vector Auto Regression (VAR) results confirmed the positive relationship between inflation and corruption in the long run. Granger causality also runs from inflation to corruption. Our finding of a significant and positive long run relationship between corruption and inflation suggests that inflation targeting may have an extra benefit of reducing corruption in the long run, a major contribution to the literature. Our finding of asymmetry in corruption's response to increases and decreases in inflation in the long run, tempers expectations about how effective inflation control strategies will be in reducing corruption. While rising inflation significantly enhances corruption, much stronger inflation-control policies are needed to check corruption. Further, since inflation undermines purchasing power, distorts economic planning, and encourages corruption in Ghana, the government must redouble efforts to tackle inflation to reduce corruption.